InAs0.9Sb0.1-based hetero-p-i-n structure grown on GaSb with high mid-infrared photodetection performance at room temperature - Tobing, Landobasa Yosef Mario (2019)
We present the design, fabrication, and characterization of middle-wavelength infrared photodetector based on active InAs0.9Sb0.1-based hetero-p-i-n structure grown on GaSb substrate. In this structure, the active absorption layer is sandwiched between thin quaternary p-type and n-type AlInAsSb layers and a heavily doped AlGaSb layer is introduced to reduce dark current. We observed good lattice matching between GaSb substrates and epitaxial layers by high-resolution X-ray diffraction. Photoluminescence (PL) spectrum at 13 K shows a full width at half maximum of ~ 29 meV, demonstrating good quality active absorption layers. The band gap energy of InAs0.9Sb0.1 is derived as ~ 0.322 eV at 0 K by Varshni fitting from PL spectra at different temperatures. A rather flat room-temperature responsivity of ~ 0.8–0.9 AW−1 over a wavelength range of ~ 2.1 µm is demonstrated without antireflection coating. A detectivity of 8.9 × 108 cm Hz1/2 W−1 at 3.5 µm for room-temperature operation is achieved under applied bias of − 0.5 V.